FAKTOR - FAKTOR YANG MEMPENGARUHI TINGKAT KEPATUHAN MASYARAKAT DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI DESA LONTOS KECAMATAN LUWUK TIMUR - Samsidar (Jurnal Ilmiah Manajemen Emor (Ekonomi Manajemen Orientasi Riset), 2024)
This research aims to determine what factors influence the level of community compliance in paying land and building taxes in Lontos Village, East Luwuk District. Based on the research results, it was found that income, tax services and tax knowledge simultaneously had a positive and significant effect on taxpayer compliance in paying land and building taxes in Lontos Village, East Luwuk District. The influence of income, tax services and tax knowledge is positive, which means that the greater the income, tax services and tax knowledge, the higher the level of taxpayer compliance in paying PBB.